Anatomy and Histology of Testes of Male Buffalo Egrets (Bubulcus Ibis) - Umartani, Lita Ayu; Rahim, Aretasani; Syahidah, Halimah Asy (Proceeding International Conference on Science and Engineering, 2019)
The buffalo egret (Bubulcus ibis) belongs to the Ciconiiformes order, family Ardeidae. The buffalo egret (Bubulcus ibis) is the smallest egret (about 50 cm). Its body is slimmer than Blekoksawah (Ardeolaspeciosa), although not as large as egrets. All feathers are white, but during the mating season the feathers on the head, neck, back and chest are yellow. Reproductive organs are the ke y to success in maintaining new offspring. Male reproductive organs will produce male sex cells or living spermatozoa. It is important to do research on anatomy and histology to determine the maturity of the reproductive organs of the bird. The purpose of this study was to determine the anatomical and histological structure of male reproductive organs of buffalo egrets (Bubulcus ibis). The method used for histology is the paraffin method with Hematoxylin-Eosin staining. The data analysis technique uses descriptive analysis for histological preparations. Anatomical observations include the color, shape and location of the reproductive organs, while histological observations of the structure of the reproductive organs using a microscope. The results of the study were anatomically pale-colored testicle. The location of the testicles is on ventral from the most cranial lobe. While the histological structure of the testis of the Buffalo Egret (Bubulcus ibis) consisted of spermatozoa, lumen, stereosilia, ephitelium of eididymis and seminiferous tubules.